Human Security: A Response to the Climate Security Debates - Elliott, Lorraine (2016)
Debates about climate change as a threat to international peace have focused on conflict, civil unrest, and the consequences for states. Human security offers an alternative, people-centred approach to understanding the security implications of climate change.